An Analysis of Women’s Subordination in Eka Kurniawan’s Magical Realism Novel Entitled Beauty is a Wound (2015) - Riksan Dani Juniardi; Nia Nafisah (Passage, 2021)
Women’s subordination is one of the most prevalent topics in the study of feminism. One of the novels that portrays the issues of women’s subordination in Indonesia is Eka Kurniawan’s magical realism novel titled Beauty is a Wound (2015). By applying descriptive qualitative approach and textual analysis method, the study analyzes how women’s subordination is portrayed in the novel based on Juliet Mitchell’s (1966) socialist feminist theory. The study found that women’s subordination occurred in four sectors of production, reproduction, sexuality, and socialization. Women’s subordination is portrayed through the men and women characters’ actions, behaviors, and thoughts. The study also found that women’s subordination in every sector is interrelated and occurs frequently in the sexuality sector. It can be implied from the portrayal that women’s subordination is a rampant issue in Indonesia, especially in terms of women’s sexuality. Keywords: Beauty is a Wound, magical realism, socialist feminism, women’s subordination